The Change in Students' Communication and Collaboration Skills Through Time Token Cooperative Learning Model - Yennita, Yennita; Al Fatihah, Annisa; Zulirfan, Zulirfan; Osman, Kamisah (Universitas Negeri Semarang, 2024)
The 21st century highlights the need for students to develop relevant abilities, such as collaboration and communication skills. Communication skills are critical for students to interact and express thoughts or ideas when solving problems. By communicating efficiently, students collaborate more easily, creating cooperation, responsibility, and concern within the group. This research aims to improve students’ communication and collaboration skills in science learning by implementing the time-token cooperative learning model. This research is a quasi-experiment with a single-group pretest-posttest design. The following is the information obtained in this research: 1) Time-token cooperative learning has an effect in improving students’ collaboration and communication skills; 2) Time-token cooperative learning has an effect in improving collaboration and communication skills for male and female students; 3) Male and female students’ collaboration skills increased after implementing the time-token model. There is an increase in communication skills in female students but not in male students, even though male students’ initial and final skills are higher than female students. Therefore, it is concluded that the time-token cooperative learning model increases students’ communication and collaboration skills.